Inclusion or Embrace?: Communion and a Theology of Embrace - Newell, Christopher (Journal of religion, disability & health, 2009)
There is a difference between simply including persons with disabilities in communities and fully embracing and welcoming them as members. Drawing on observations of the architecture of a particular worship space and the priest leading worship, the author considers the ways in which communion reveals both how near and how far we are from fully embracing all people—including persons with disabilities—as members in and leaders of the Body of Christ.